„Lieber Niembsch“ oder: Der Dichter im Gehäus. Anmerkungen zu Manfred Karges Spiel mit Biographie und Geschichte um den Autor im „Stadium der Verrücktheit“ - Eke, Norbert Otto (Lenau-Forum)

Vergangene Zeiten. Anmerkungen zur Semantik des Umbruchs und zu den Bedeutungsstrukturen im historischen Erzählen der frühen Restaurationszeit (1815-1830) - Eke, Norbert Otto (Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit)

Der historische Roman der frühen Restaurationszeit. Zur Einführung - Eke, Norbert Otto; Steinecke, Hartmut (Geschichten aus (der) Geschichte. Zum Stand des historischen Erzählens im Deutschland der frühen Restaurationszeit)

Graph Gramars and Their Application to Computer Science, 5th International Workshop (1994), Selected Papers

Berücksichtigung von Datenschutzaspekten in einem bevölkerungsbezogenen Krebsregister - Thoben, Wilfried; Appelrath, Hans-Jürgen; Rettig, Jens; Sauer, Stefan (Proceedings of the conference on Medizin und Information, Biometrie und Epidemiologie (GMDS 1994), Dresden (Germany))
Die Pilotphase 1993/ 94 zum Aufbau eines Niedersächsischen Krebsregister untersucht das im Entwurf des Bundeskrebsregistergesetzes vorgesehen Modell für ein bevölkerungsbezogenes Krebsregister. Darin werden die Krebsmeldungen in einer Vertrauensstelle erfaßt und die personenidentifizierenden Daten vor der Übermittlung an die Registerstelle anonymisiert, wo sie dann zu einem bevölkerungsbezogenen Krebsregister verdichtet und epidemiologischer Forschung zur Verfügung gestellt werden ([1], [2], [3]). Dieses sogenannte „Michaelis“-Modell erlaubt eine bevölkerungsbezogene Registrierung von Krebsfällen unter Berücksichtigung datenschutzrechtlicher Aspekte („Informationelles Selbstbestimmungsrecht“) der einzelnen Betroffenen. In vier Teilprojekten werden dabei in der Modellregion Weser-Ems die Integration krebsregistrierender Einrichtungen, die Chiffrierung/ Dechiffrierung von Krebsmeldungen, der Abgleich anonymisierter Meldungen in der Registerstelle und die Entwicklung eines epidemiologischen Informationssystem betrachtet ([4], [5]).

Optical Modelling, Simulation and Improvement of PV Module Encapsulation - Krauter, Stefan; Hanitsch, Rolf; Campbell, P.; Wenham, S.R. (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1198–1201)

Simulation Tool for Prediction and Optimization of Output Power Considering Thermal and Optical Parameters of PV Module Encapsulation - Strauss, Philipp; Onneken, K.; Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1194–1197.)

Einfluß optischer und thermischer Parameter auf den Tageswirkungsgrad von photovoltaischen Modulen - Krauter, Stefan; Hanitsch, Rolf (Neuntes Internationales Sonnenforum, Berlin (Deutschland), 28. Juni – 1. Juli 1994, S. 495–502)

Simulation of Thermal and Optical Performance of PV Modules - Krauter, Stefan; Hanitsch, Rolf; Wenham, S. R. (Proceedings of the 3rd World Renewable Energy Congress, Reading (UK), 11.–16. September 1994)

Actual Optical and Thermal Performance of PV-Modules - Krauter, Stefan (Proceedings of the 1st World Conference on Photovoltaic Energy Conversion (Joint Congress of IEEE/PVSEC/EUPVSEC), Waikoloa, Hawaii (USA), 5.–9. Dezember 1994, S. 734–737.)

Syntax and Semantics of Hybrid Database Languages - Andries, Marc; Engels, Gregor (Proceedings of the International Workshop on Graph Transformations in Computer Science (1993), Dagstuhl (Germany))
We present the hybrid query language HQL/EER for an Extended Entity-Relationship model. As its main characteristic, this language allows a user to freely mix graphical and textual formulation of a query. We show how syntax and semantics of this hybrid language are formally defined by means of a slightly extended version of PROGRES, a specification formalism based on programmed and attributed graph rewriting systems.

Specification of coordinated behaviour by SOCCA - Engels, Gregor; Groenewegen, Luuk (Proceedings of the Third European Workshop on Software Process Technology (EWSPT 1994), Villard de Lans (France))

Windatlas für das PESAG-Versorgungsgebiet - Bendfeld, Jörg; Ernst, Achim; Ortjohann, Egon

Flächendeckende Windpotentialbestimmung in einer Binnenlandregion mit ausgeprägter Orographie - Bendfeld, Jörg; Ernst, Achim; Ortjohann, Egon; Langrock, Beate; Scholz, Norbert (Renergie 94 - Windenergienutzung im Binnenland, Solarenergienutzung in Deutschland)

Improvements in beam search for 10000-word continuous-speech recognition - Haeb-Umbach, Reinhold; Ney, Hermann (IEEE Transactions on Speech and Audio Processing)
The authors describe the improvements in a time-synchronous beam search strategy for a 10000-word continuous-speech recognition task. Basically they introduced two measures, namely a tree organization of the pronunciation lexicon and a novel look-ahead technique at the phoneme level. The experimental tests performed showed that the number of state hypotheses could be reduced from 50000 to 3000, i.e., by a factor of about 17. At the same time, the word error rate did not increase.

Progress in Large-Vocabulary, Continuous Speech Recognition - Ney, Hermann; Steinbeiss, Volker; Aubert, Xavier L.; Haeb-Umbach, Reinhold (Artifical Intelligence, Progress and Prospects of Speech Research and Technology, Munich)

An Overview of the Philips Research System for Large Vocabulary Continuous Speech Recognition - Ney, Hermann; Steinbeiss, Volker; Haeb-Umbach, Reinhold; Tran, Bach Hiep (International Journal on Pattern Recognition and Artificial Intelligence)
This paper gives an overview of a research system for phoneme based, large vocabulary continuous speech recognition. The system to be described has been applied to the SPICOS task, the DARPA RM task and a 12000 word dictation task. Experimental results for these three tasks will be presented. Like many other systems, the recognition architecture is based on an integrated statistical approach. In this paper, we describe the characteristic features of the system as opposed to other systems: (1) The Viterbi criterion is consistently applied both in training and testing. (2) Continuous mixture densities are used without any tying or smoothing; this approach can be viewed as a sort of statistical template matching. (3) Time-synchronous beam search is used consistently throughout all tasks; extensions using a tree organization of the vocabulary and phoneme lookahead are presented so that a 12000 word task can be handled.

Synthesis for Off-line Testability - Hellebrand, Sybille; Juergensen, Arne; Wunderlich, Hans-Joachim

Chip Level Test Planning for Controlling the Tradeoff between Hardware Overhead and Test Time - Hellebrand, Sybille; Juergensen, Arne; Stroele, Albrecht; Wunderlich, Hans-Joachim

Effiziente Testsatzkodierung für Prüfpfad-basierte Selbsttestarchitekturen - Venkataraman, Srikanth; Rajski, Janusz; Hellebrand, Sybille; Tarnick, Steffen
Keywords: WORKSHOP